Disaffordances And Dysaffordances In Code - Wittkower, D.E (AoIR Selected Papers of Internet Research, 2017)
Landon Winner has argued that ‘artifacts have politics’, demonstrating that code can have discriminatory effects, but work in philosophy of technology has not identified what kinds of user exclusion constitute an injustice. Previous theoretical work on affordances has also left non-affordances substantially untheorized, providing no clear basis for distinguishing problematic from unproblematic non-affordances. This paper presents a three-fold division of non-affordances as exclusionary of users due to (a.i) unproblematic mutually exclusive proper functions, due to (a.ii) unproblematic demographically distributed service provision, and due to (b) problematic discriminatory exclusion. Within this third category, two kinds of discriminatory exclusion are identified: (b.i) direct exclusion through interfaces that do not accommodate relevant user groups, and (b.ii) indirect exclusion through recapitulation of existing social prejudices. Within discriminatory forms of exclusion, (b), two modalities of exclusion are identified: disaffordance and dysaffordance. In the former, code fails to recognize relevant user identity groups; in the latter, code additionally requires unaccommodated users to misrepresent themselves in order to gain access to product functions. These forms of discriminatory code are illustrated using a series of examples, including user profile data entry fields, ‘flesh-colored’ crayons, kitchen counters, strollers, calendars, and gendered RPG game-play design. Through this theorization of non-accommodation, the paper seeks to provide tools to designers to avoid discriminatory code, and to provide tools to critics and activists to argue more forcefully for reform of discriminatory code.